Variational Auto-Encoder based Mandarin Speech Cloning - Xing, Qingyu; Ma, Xiaohan (arXiv.org, 2022)
Speech cloning technology is becoming more sophisticated thanks to the advances in machine learning. Researchers have successfully implemented natural-sounding English speech synthesis and good English speech cloning by some effective models. However, because of prosodic phrasing and large character set of Mandarin, Chinese utilization of these models is not yet complete. By creating a new dataset and replacing Tacotron synthesizer with VAENAR-TTS, we improved the existing speech cloning technique CV2TTS to almost real-time speech cloning while guaranteeing synthesis quality. In the process, we customized the subjective tests of synthesis quality assessment by attaching various scenarios, so that subjects focus on the differences between voice and our improvements maybe were more advantageous to practical applications. The results of the A/B test, real-time factor (RTF) and 2.74 mean opinion score (MOS) in terms of naturalness and similarity, reflect the real-time high-quality Mandarin speech cloning we achieved.